Evaluasi Program Layanan Perlindungan Anak Usia Dini Holistik Integratif dalam Pencegahan Kekerasan Anak di Kabupaten Sidoarjo - Sahri, Rosalina Berliana Permata; Murti, Indah; Puspaningtyas, Anggraeny (Universitas 17 Agustus 1945 Surabaya, 2026)
The high number of cases of violence against children in Sidoarjo Regency demands the strengthening of protection services in the implementation of Integrative Holistic Early Childhood Education. This study aims to evaluate the protection services of Integrative Holistic PAUD in the prevention of violence against children using the CIPP (Context, Input, Process, Product) evaluation model. The research was carried out with a qualitative descriptive approach through interviews, observations, and documentation at related agencies and three PAUD HI units in Sidoarjo Regency. The results of the study show that in the context, the program already has an adequate regulatory basis, but the understanding of non-violent parenting is uneven. In terms of input, the qualifications of educators are quite good, but training, facilities, and child protection budgets are still limited. In terms of process, socialization and parenting activities have been running, although cross-sector coordination has not been optimal. In terms of products, the program raises awareness of children's rights and creates a safer learning environment, but the impact is uneven. These findings imply the need for strengthening regulations, dedicated funding, ongoing training, and cross-sectoral coordination to make IPR PAUD protection services more effective.